The Question of Transformation in the English Language Education Classroom - Sharma, Netra Prasad (Rupantaran: A Multidisciplinary Journal, 2020)
Have we transformed ourselves? The question that frequently arises in the discourse pertaining to the reintroduction of the semester system in the different faculties of Tribhuvan University has taken the shape of this paper that attempts to probe into the demeanour of both teachers and students in the English language education classrooms in the Kathmandu valley. The data collected through a brief survey of student opinions and informal discussion with concerned teachers portray the classroom scenarios that are difficult to differentiate from the ones that usually characterize the classrooms in the “annual system” of teaching and testing. This portrayal suggests the future course of action on the part of teachers and students both.